PENCEGAHAN STUNTING MELALUI BUDAYA SEHAT: SUKSES IMPLEMENTASI CTPS DI KELURAHAN NAIBONAT - Marni Marni; Anderias Umbu Roga; Christina Rony Nayoan; Intje Picauly (Jurnal Pengabdian pada Masyarakat Kepulauan Lahan Kering, 2023)
One of the activities in the Naibonat Village that needs special attention is the prevention of stunting through the application of a healthy culture and the practice of washing hands with soap (CTPS). The history of PkM activities highlights the high incidence of stunting in this kelurahan, reaching 15.8% of the total number of children under five assessed. PkM stunting prevention activities will be carried out in July 2023 with an emphasis on increasing public awareness of stunting, CTPS procedures, use of local media, and the active participation of regional leaders. The results of this Community Service show that effective health education has increased public awareness of stunting from 69.7% to 92.3%. After this program, there was a sharp increase in the use of soap, from 30% to more than 80%. The dissemination of health messages has also benefited from the increased use of local media, particularly leaflets featuring dialects of the local culture. In addition, the community is also increasingly encouraged by community leaders who actively promote good hand washing habits. To ensure the continuity and sustainability of the program in preventing stunting and improving public health in Kelurahan Naibonat, recommendations include increased health education, ongoing collaboration with community leaders, ongoing monitoring and evaluation, and active community involvement.